Financial Literacy Among Female Entrepreneurs in Ghana: Evidence from Traditional Markets - Ahiase, Godwin; Sari, Maya; Nugraha, Nugraha; Andriana, Denny; Kpodo, Percy Chris; Ampomah, Philipina (Universitas Pendidikan Indonesia, 2024)
This study examines the financial behaviour and utilisation of e-finance among female entrepreneurs in traditional marketplaces in Ghana. The researchers collected data from 385 female entrepreneurs using a quantitative research method. The data was collected through a descriptive survey design and analysed using ordinary least squares regression models. The results show significant correlations between e-finance adoption, financial literacy, and financial behaviour. This highlights the importance of financial literacy in enabling women to participate in the market. The study also found that financial literacy had a greater impact on the financial behaviour of younger women, suggesting the need for targeted interventions that leverage technology. Additionally, the study found that the level of education had a significant impact on the adoption of electronic finance. This emphasises the importance of improving digital literacy to bridge the skills divide. Based on these findings, the study suggests the need for tailored financial education programmes and comprehensive initiatives to promote responsible financial practices and the adoption of modern financial technologies by female entrepreneurs in traditional markets.